The equation of a line in point slope form =
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
To put
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
into function notation, we need to get y by its self.
Lets say we had a point (2,2) and a slope of 3. Ok, now that we have our point and slope, lets turn point slope form into function notation.
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
![y - 2 = 3(x - 2)](https://tex.z-dn.net/?f=y%20-%202%20%3D%203%28x%20-%202%29)
![y - 2 = 3x - 6](https://tex.z-dn.net/?f=y%20-%202%20%3D%203x%20-%206)
![y = 3x - 6 + 2](https://tex.z-dn.net/?f=y%20%3D%203x%20-%206%20%2B%202)
![y = 3x - 8](https://tex.z-dn.net/?f=y%20%3D%203x%20-%208)
Change the y to f(x)
![f(x) = 3x - 8](https://tex.z-dn.net/?f=f%28x%29%20%3D%203x%20-%208)
<-----Function notation.
Answer:
it would be A.
Step-by-step explanation:
HIUSHISGSOUCOUVCVC
Answer:
Step-by-step explanation:
Edit: how do i delete my answer?
![\huge\boxed{x=-6}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bx%3D-6%7D)
Hey there! Our goal here is to isolate the variable on one side of the equation.
![\begin{aligned}-7(x+6)&=4(x+6)&&\smash{\Big|}&&\textsf{Start with the original equation.}\\-7x+(-7)(6)&=4x+4(6)&&\smash{\Big|}&&\textsf{Distribute.}\\-7x-42&=4x+24&&\smash{\Big|}&&\textsf{Multiply.}\\-7x-4x&=24+42&&\smash{\Big|}&&\textsf{Move the terms.}\\-11x&=66&&\smash{\Big|}&&\textsf{Combine like terms.}\\x&=\boxed{-6}&&\smash{\Big|}&&\textsf{Divide both sides by $-11$.}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D-7%28x%2B6%29%26%3D4%28x%2B6%29%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BStart%20with%20the%20original%20equation.%7D%5C%5C-7x%2B%28-7%29%286%29%26%3D4x%2B4%286%29%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BDistribute.%7D%5C%5C-7x-42%26%3D4x%2B24%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BMultiply.%7D%5C%5C-7x-4x%26%3D24%2B42%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BMove%20the%20terms.%7D%5C%5C-11x%26%3D66%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BCombine%20like%20terms.%7D%5C%5Cx%26%3D%5Cboxed%7B-6%7D%26%26%5Csmash%7B%5CBig%7C%7D%26%26%5Ctextsf%7BDivide%20both%20sides%20by%20%24-11%24.%7D%5Cend%7Baligned%7D)
Answer:
there are 3 red fish
Step-by-step explanation:
1:5
_:15
5 times 3 =15
so 1 times 3 =3